(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research study focuses on the key competencies of automobile professional which could affect the organizational effectiveness. The Composition of people which formulate independent business identity for some specific purpose is commonly known as organization and getting desired outcome within defined resources is treated as effectiveness. The aim and objective of the study was to reconnoiter the relationship between competency-based performance management and organizational effectiveness (OE). The empirical research was undertaken by the researcher to analyses and identify the competency levels of executives, identify the executive’s competencies through competency modelling and identify the performance standards of executives through structured questionnaire and has chosen three manufacturing units for the purpose of the analysis. The purpose of this study was to identify the causal relationships between the competencies of managing self, managing others and business management with management competency model. The research design involved developing scale for “competency-based superior performance” and validating scale for “organizational effectiveness,” The data for this survey were collected from 720 respondents through structured questionnaire. The main hypothesis of the study is to know the relationship between employee competency and organizational and job performance and Employee competency mediates the relationship between transformational leadership style and organization performance. Hypotheses are depicting aforementioned relationships were empirically tested in the context of competency-based performance practices in automobile companies in India. Structural Equation Modeling is a comprehensive statistical approach for testing the hypotheses on the relationships between the manifest variables and latent variables, sometimes called covariance structure analysis, causal modeling or Lisrel modeling. The empirical results provide methods to accelerate the performance management initiatives based on a leadership competency model, which are necessary for building performance culture in the organization. This study contributes by developing a new scale for measuring competency-based performance practices. A positive relationship between competency-based superior performance and Organizational Effectiveness with productivity, adaptability and flexibility has been empirically confirmed using SEM. The developed model will act as a building block for performance measurement in organizations. This study promotes leadership competency model to be applied in creating a performance- based culture. It is a unique attempt to test the relationship between competency-based performance management and Organizational Effectiveness.